State feedback containment control of multi-agents system with lipschitz nonlinearity - Siti Nurfarihah Sheikh Hanis; Ahmad Sadhiqin Mohd Isira; Azdiana Md Yusop; Mohd Hendra Hairi; Wong Chunyan; Cherry D. Casuat; Zaiton Abdul Mutalip (Institute of Advanced Engineering and Science, 2021)
This paper studies the containment control problem of the leader-follower configuration in a multi-agents system included with a type of nonlinearity such as Lipschitz with respect to continuous-time and directed spanning forest communication network topology. A state feedback containment controller is designed and proposed with control theory and the Laplacian network structure where it utilizes the relative information of each agent. The controller designed ensures that the followers are contained by the leaders that form the convex hull formation. For the containment to happen, a minimum of one leader is needed to have a direct communication trajectory to the followers. Lyapunov stability theory is used to provide the stability conditions after analyzing the network structure. Finally, it has been shown from simulation that the followers are contained successfully with the proposed controller.